Chapter Bruno Trentin al Parlamento europeo: macroeconomia ed elementi di socialismo - Mari, Giovanni (Studi e saggi, 2023)
The essay focuses on Trentin's theoretical elaboration and action in the European Parliament. Starting with his involvement in the "Spinelli Group," it analyzes the relationship between work and knowledge conceived as an in-depth study of the Lisbon program from the perspective of labor and its transformations. The socio-economic program, which was supposed to become an essential part of the program of the European Socialists for the 2004 elections, on which Trentin works, is analyzed in relation to his coeval writings (La libertà viene prima (2004) and the Keynote Lecture given at Ca'Foscari in 2002). The essay highlights the link between knowledge economy, lifelong learning, elements of socialism and analyzes the tools envisaged for the strengthening of a transparent economic governance, at the European level, in dialogue with the social partners capable of leading to a federal socialism.